Corporate Reputation and the News Media: The Origin Story. Issue 3 (November 2017) - Carroll, Craig
Abstract This essay provides the background story on the role that Corporate Reputation Review and its conference, Corporate Reputation, Identity, and Competitiveness played in my research and thinking on corporate reputation as a scholarly endeavor. In particular, this essay discusses the 3rd conference, (including access to the papers, presentations, and speakers), offline discussions with attendees, and the meeting of the minds between Fombrun, van Riel, and Max McCombs, one of the co-authors of the original study on agenda-setting theory. A brief description of the pivotal projects and outcomes of that meeting are discussed.